The Product Innovation of Market Orientation to Marketing Performance in Indonesia Tourist Destination - ., HERSUGONDO; WAHYUDI, SUGENG; LAKSANA, RIO DHANI (Journal of Ecohumanism, 2024)
The present study aims to investigate the impact of product innovation on marketing performance of SME’S souvenirs in Indonesia. The study’s findings suggest that there is a favorable and substantial relationship between product innovation and marketing performance. The relationship between market orientation and marketing performance is mediated by product innovation. This study used two analysis techniques: descriptive and inferential statistics. Although inferential statistics are used to assess the validity of hypotheses developed using route analysis techniques in conjunction with the Sobel Test, descriptive statistics seek to identify the traits and answers of respondents with reference to the statement items in the questionnaire which indicates that product innovation can mediate the influence of market orientation on marketing performance. The higher the impact of market orientation on enhancing marketing performance throughout SME’s souvenir in Indonesia, the better the product innovation. Market orientation significantly and favorably influences both product innovation and marketing effectiveness.